Generation Gap from Family Orientation Point of View: A Case on PT. Panggung Jaya Indah Textile - agustina, karina enny; Bawazir, Fatmah Cholid; Linawati (Universitas Ciputra Surabaya, 2023)
Family businesses account for 95 percent of all existing businesses in Indonesia, but only 12 percent survived to the third generation. The occurrence of various conflicts, differences, and problems in the family business gave rise to a well-known social stigma: the first generation builds, the second generation enjoys, and the third generation destroys. In this literature, the authors wish to examine the generation gap that exists at PT. Panggung Jaya Indah Textile/ PT Pajitex, a sarong manufacturer company with the brand